Evaluation of Paperless Electronic Data Entry and its Comparison with Manual Entry Method for Oral Health Assessment of Adults - Manu Batra; Deeksha Gijwani; Hansika Popli (Indian Journal of Dental Research)
Introduction: World Health Organization oral health assessment forms (2013) are the standard method to record the information regarding oral health among children and adults. Conventional paper forms are still being used and data are entered in digital form manually for further statistical analysis, which causes duplication, errors, and extra time consumption. Hence, the aim of present study was to conduct a usability evaluation of the novel offline Paperless Electronic Data Entry System (PEDES) and compare it with the manual entry method (MEM) for the World Health Organization oral health assessment form (2013) for adults. Materials and Method: A total of 186 participants were enrolled for the study as recorders. Usability evaluation was assessed using a user experience questionnaire (UEQ). Each participant used manual and electronic data entry to work through five documented tasks. The usability of the paperless entry system was evaluated with the UEQ tool. Results: Time taken to complete adult form was less for PEDES as compared to MEM (P < .001). UEQ scores for all scales under attractiveness, pragmatic, and hedonic quality were found to be good with a value more than 0.8. Comparison of the task completion among PEDES and MEM for the different task assigned under different domains showed statistically significant differences (P < .05). Conclusion: The study strongly recommends the usage of this novel technique in future, so that labour-intensive manual data entry can be replaced with a more effective method. Being offline system, it has an additional edge with no requirement of active internet to record or store the data.